Synthesis, Characterization of Iron Oxide (Î‘-Fe2o3) Nanoparticles and its Application in Photocatalytic Reduction of Cadmium (Ii) - H Gurlhosur, Shrikrishna; Sreekanth B, Dr; ., . (International Journal of Engineering and Technology, 2018)
The Î±-Fe2O3 Nanoparticles were successfully synthesized by Sol-Gel method and the powder was calcinated at 4000. SEM, XRD, FTIR, EDX studies were carried out for characterization. The XRD confirmed that nanoparticles were Hematite (Î±-Fe2O3 ) havingÂ crystalline size of 11.55nm which confirms the Hematite(Î±-Fe2O3) on comparison with obtained spectra against Joint Committee on Powder Diffraction Standards Database(JCPDS) and SEM morphology indicated thatÂ IronOxide Nanoparticles were of flower shape at higher magnifications . The FTIR showed the bonds between functional groups and Fe-O group, O-H bending and vibration bonds. The presenceÂ ofÂ FeO, Fe, C, in nanomaterial was confirmed by EDX . Synthesized iron oxide Î±-Fe2O3 (Hematite) crystalline size of 11.55nm was used in the study of photo catalytic reduction of Cadmium (II) .Different parameters like Metal concentration, Dosage of Nanoparticles, Contact time and pH were studied. pH maintained for the solutions of different concentrations were 4,5,6,7 and 10. Concentration of cadmium solution taken for the study were 2,4,6,8 and 10ppm. Keeping concentration and dosage constant, pH was varied. Then concentration was varied by keeping dosage and pH constant. Then dosage was varied by keeping concentration and pH constant. Dosage of iron oxide taken was 50 mg, 75mg, 100mg, 125 mg and 150mg. It was observed that photo catalytic reduction by Iron oxide nanoparticles (IONP)Â wasÂ more effective at metal concentration 4ppm, IONP dosage 100mg, pH 5, and contact time of 150 min with 97.02%Â reduction of Cadmium (II).Â